Reverse phase high performance liquid chromatographic determination of mefenamic acid in human plasma using liquid-liquid extraction technique - Helal Uddin, A.B.M.; Mohamad, Huda Jamilah; Alaama, Mohammed; Amiruddin, Noor Syafawati (2014)

(untitled)
Mefenamic Acid (MA) is a non-steroidal anti-inflammatory drug (NSAIDs). It is a class of drug that provides analgesic and antipyretic (fever reducing effect) and in higher doses, anti-inflammatory effect. This study is focused to develop a rapid and sensitive method for the detection of mefenamic acid in human plasma. Liquid - liquid extraction was used as the technique to extract the mefenamic acid from human plasma. Several solvents were used such as: dichloromethane(Dcm), dichloromethane:isopropylpropanol (80:20) (DCM-IPA) and ethyl acetate. It was found that dichloromethane and ethyl acetate produce good recovery. Several buffers were used to facilitate the extraction of the analyte. Among them, ammonium acetate buffer with pH 3.9 produced better isolation of the mefenamic acid as well as recovery compared to others. Chromatographic separation was achieved by Agilent Zorbax Eclipse XDB-C18 (150 mm x 4.6 mm, i.d 3.5µm) with a mobile phase consisting of acetonitrile and 2% triethylamine (pH was adjusted to 4.2 with phosphoric acid) in a ratio of 60:40. The retention time for mefenamic acid and diclofenac was 5.9 and 3.9 minutes respectively. Diclofenac sodium was used as internal standard for this study.